Recontextualization Practices of Nepalese Language in Educational Policy Discourses - Budha, Dhan Bahadur (Journal of Jayaprithvi Multiple Campus, 2025)
Language in education policy discourses keep on changing periodically in the history of formal education of a nation-state due to the ideological influence oriented by national and international level of sociopolitical change. To discuss such issues, this paper theoretically analyzes Nepalese language in education policy provisions since 1956 to present, which are mentioned in different constitutional and educational policy discourses, to explore how those policy discourses are recontextualized under the influence of hegemonic political power, neoliberalism, globalization and linguistic human right-based ideologies in the formation process. The finding shows that there is strong influence of hegemonic political power before 1990, but the subsequent policy discourses indicate that there is greater influence of linguistic human right-based ideology along with globalization and neoliberalism in democratic period. Therefore, the study is beneficial for policy makers, implementors and researchers to enlighten how ideological visions influence language in education policy formation process of a country. Finally, this study provides some insightful thoughts to conduct further research studies in this domain to develop broader comprehensive overviews.